Pathophysiology practical classes. Module 1. General Pathophysiology - Kolesnik, Y. M.; Melnikova, O. V.; Abramov, A. V.; Zhulinsky, V. A.; Колесник, Юрій Михайлович; Мельнікова, Ольга Валеріївна; Абрамов, Андрій Володимирович; Жулінський, Володимир Олександрович (Zaporozhye state medical university, 2015)
This manual was written according to the program of pathophysiology worked out by the Ministry of Health of Ukraine (Kiev, 2006). It includes plan of lectures and practical classes, instruction for every practical class, list of topics for independent studying, information about rating estimation of students’ knowledge. Instruction for practical classes include: questions for preparing, description of experimental work, place for results registration and analysis. It can be used by the student of medical faculty while studying pathophysiology.
Посібник підготовлений у відповідності до програми з патофізіології для студентів вищих медичних навчальних закладів III-IV рівнів акредитації (2006 р). і містить плани лекцій та практичних занять, перелік тем для самостійного вивчення, питання до кожного практичного заняття, методику проведення експериментальних робіт, місце для обліку та оцінки результатів проведених експериментів, ситуаційні задачі для розв’язування. Навчально-методичний посібник може бути використаний під час вивчення патофізіології студентами медичного факультету, які навчаються англійською мовою.
Keywords: pathophysiology; патофізіологія; патофизиология